Introduction to Food Chemistry - Owusu-Apenten, Richard (CRC PRESS, 2005)
Providing a thorough introduction to a core area specified by the Institute of Food Science, Introduction to Food Chemistry focuses on principles rather than commodities and balances facts and explanations." "This multilevel text presents a wealth of information in a clear and accessible style. It serves as an ideal introduction to a diverse audience, as well as a supplementary textbook for undergraduate and graduate students in food science courses.